The causes and consequences of seasonal variation in COPD exacerbations - Donaldson, Gavin C (Dove Medical Press, 2014)
The time of year when patients experience exacerbations of chronic obstructive pulmonary disease is a much-overlooked feature of the disease. The higher incidence of exacerbations in winter has important consequences for patients in terms of increased morbidity and mortality. The seasonality also imposes a considerable burden on already-overloaded health care services, with both primary care consultations and hospital admissions increasing in number. The seasonality of exacerbations varies with latitude, and is greater in more temperate climates, where there may be less protection from outdoor and indoor cold exposure. The precise causes of the seasonality are unknown, but thought to be partly due to the increased prevalence of respiratory viral infections circulating in cold, damp conditions. Increased susceptibility to viral infection may also be a mechanism mediated through increased airway inflammation or possibly reduced vitamin D levels. The seasonality of exacerbations informs us about the triggers of exacerbations and suggests possible strategies to reduce their number.